Use of psycho‐oncological services by prostate cancer patients: A multilevel analysis. (31st March 2020) - Breidenbach, Clara; Roth, Rebecca; Ansmann, Lena; Wesselmann, Simone; Dieng, Sebastian; Carl, Ernst‐Günther; Feick, Günter; Oesterle, Alisa; Bach, Peter; Beyer, Burkhard; Borowitz, Rainer; Erdmann, Jörg; et al.
Abstract: Background: Cancer patients often suffer from psychological distress. Psycho‐oncological services (POS) have been established in some health care systems in order to address such issues. This study aims to identify patient and center characteristics that elucidate the use of POS by patients in prostate cancer centers (PCCs). Methods: Center‐reported certification and patient survey data from 3094 patients in 44 certified PCCs in Germany were gathered in the observational study (Prostate Cancer Outcomes). A multilevel analysis was conducted. Results: Model 1 showed that utilization of POS in PCCs is associated with patients' age (OR = 0.98; 95%‐CI = 0.96‐0.99; P < .001), number of comorbidities (1‐2 vs 0, OR = 1.27; 95%‐CI = 1.00‐1.60; P =.048), disease staging (localized high‐risk vs localized intermediate risk, OR = 1.41; 95%‐CI = 1.14‐1.74; P < .001), receiving androgen deprivation therapy before study inclusion (OR = 0.19; 95%‐CI = 0.10‐0.34; P < .001), and hospital teaching status (university vs academic, OR = 0.09; 95%‐CI = 0.02‐0.55; P = .009). Model 2 additionally includes information on treatment after study inclusion and shows that after inclusion, patients who receive primary radiotherapy (OR = 0.05; 95%‐CI = 0.03‐0.10; P < .001) or undergo active surveillance/watchful waiting (OR = 0.06; 95%‐CI = 0.02‐0.15; P < .001) are less likely to utilize POS than patients who undergo radical prostatectomy. Disease staging (localized high‐risk vs localized intermediate risk, OR = 1.31; 95%‐CI = 1.05‐1.62; P = .02) and teaching status (university vs academic, OR = 0.08; 95%‐CI = 0.01‐0.65; P = .02) are also significant predictors for POS use. The second model did not identify any other significant patient characteristics. Conclusions: Future research should explore the role of institutional teaching status and whether associations with therapy after study inclusion are due to treatment effects – for example, less need following radiotherapy – or because access to POS is more difficult for those receiving radiotherapy. Abstract : The paper identifies patient and center characteristics that account for the use of psycho‐oncological services by prostate cancer patients in certified prostate cancer centers in Germany. Multilevel analysis was conducted. The results indicate that the varying utilization of psycho‐oncological services in certified prostate cancer centers may be better explained by characteristics of the centers and the patients' clinical characteristics, rather than by the patients' sociodemographic features.